2013
DOI: 10.5101/nbe.v5i1.p46-49
|View full text |Cite
|
Sign up to set email alerts
|

Cerium Oxide Nanoparticles Protects Gastrointestinal Mucosa From Ethanol Induced Gastric Ulcers in In-Vivo Animal Model

Abstract: Cerium oxide (CeO 2 ) nanoparticles having size range of 160 nm were prepared by using simple and effective sol-gel process and evaluated for their ulcer protective activity in an animal model. CeO 2 nanoparticles at a dose of 1mg/kg found to protect gastrointestinal mucosal from ethanol induced gastric ulcers. The ability of these nanoparticles to protect ethanol induced ulcers could be supported by increased amount of biomarkers in the native tissue like superoxide dismutase (SOD) (from 85.18 ± 0.24 to 103.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 17 publications
0
13
0
2
Order By: Relevance
“…Expanding on the promising results from in vitro studies, CNPs have been evaluated in vivo for their efficacy as treatments in a variety of disease states, with potential medicinal applications ranging from reproductive [ 87 ] to gastrointestinal [ 88 ] to ophthalmologic [ 76 , 89 , 90 , 91 ] and to neurological [ 66 , 92 ] health. Animal and plant models have been used to assess both the potential therapeutic benefits and the potential toxicity of CNPs either intentionally administered or unintentionally present in the environment.…”
Section: Cnp Antioxidant Activity—evidence From In Vivo mentioning
confidence: 99%
See 1 more Smart Citation
“…Expanding on the promising results from in vitro studies, CNPs have been evaluated in vivo for their efficacy as treatments in a variety of disease states, with potential medicinal applications ranging from reproductive [ 87 ] to gastrointestinal [ 88 ] to ophthalmologic [ 76 , 89 , 90 , 91 ] and to neurological [ 66 , 92 ] health. Animal and plant models have been used to assess both the potential therapeutic benefits and the potential toxicity of CNPs either intentionally administered or unintentionally present in the environment.…”
Section: Cnp Antioxidant Activity—evidence From In Vivo mentioning
confidence: 99%
“…Similarly, mice injected with human malignant melanoma cells and treated with CNPs had ≥70% reduction in tumor volume and weight compared to control studies [ 112 ]. Further work has shown that treatment with CNPs can protect gastrointestinal mucosa from oxidative damage in rats with ethanol-induced gastric ulcers [ 88 ]. One preliminary study even suggests that the antioxidant properties of CNPs could be used to combat obesity, noting an initial reduction in the body weight of rats over the first 3 weeks of the study and with an overall increase in weight of just 2% in total body weight over the 6 weeks of the study compared to a 13% increase in the weight of control rats over the same time period [ 113 ].…”
Section: Cnp Antioxidant Activity—evidence From In Vivo mentioning
confidence: 99%
“…Expanding the promising results obtained from in vitro studies, cerium oxide nanoparticles were also tested in different in vivo disease models, ranging from ophthalmologic disease to gastrointestinal and to neurological conditions …”
Section: Redox‐active Nanoparticlesmentioning
confidence: 99%
“…Відомо, що нанокристалічний діоксид церію (НДЦ) має антиоксидантні властивості [8]. НДЦ можна розглядати як потенційний геропротектор.…”
Section: вступunclassified
“…Таким чином, НДЦ покращував морфологічний стан слизової оболонки товстої кишки. Отримані результати, очевидно, можна пояснити його антиоксидантними властивостями, підтвердженням яких є відомі літературні дані [8], а також прокінетичною і, можливо, пребіотичною дією, оскільки за таких умов зменшується час контакту токсичних речовин (індолу і скатолу) зі слизовою оболонкою товстої кишки.…”
Section: результати та їх обговоренняunclassified